Product Knowledge and Halal Certification as Determinants of Halal Pharmaceutical Purchase Behavior - Ashari, Mela (Halal Science, 2025)
This study examines the impact of product knowledge and halal certification on consumers' purchase decisions for pharmaceutical products in Mojorejo Village, Madiun. Using a quantitative associative approach, data were collected from 100 respondents through questionnaires and interviews, employing stratified random sampling based on educational level. The research applied multiple linear regression analysis to examine the direct and combined effects of the independent variables on purchasing behavior. Results indicate that both product knowledge and halal certification have a significant positive influence on purchase decisions, both individually and simultaneously. The regression model yielded an R² value of 0.542, indicating that the independent variables explain 54.2% of the variance in purchasing decisions. Classical assumption tests confirmed the validity and reliability of the regression model. These findings suggest that pharmaceutical companies and health regulators should prioritize transparent halal certification and educational outreach, while policymakers can improve access to verified halal-certified pharmaceuticals.